DEVELOPMENT AND VALIDATION OF AN INSTRUMENT TO MEASURE SOCIAL CONSTRUCTIVISM IN A VIRTUAL CLASSROOM - Finch, Karuna Samuel (PUPIL: International Journal of Teaching, Education and Learning, 2021)
Virtual learning has never been an option for secondary education, but the pandemic situations have blurred this line. A considerable population of school students has been attending school from home for roughly five months now. Social Constructivist pedagogy is the need of the hour and, multiple research focussed on effective teaching and learning have endorsed it. Presently, there are no validated Instruments that, can measure and monitor the Social Constructivist domain, in a synchronous virtual classroom. This study discusses an Instrument developed to measure the social constructivist dimension of a virtual classroom in light of the concepts of Social Constructivism and Cybergogy. This paper includes an assessment of the pilot study. The evidence for the validity (Cronbach's alpha) and construct reliability of this Instrument assure that the presented assessment tool is well suited to measure the Social Constructivist dimension of a secondary level virtual classroom.